Prevalence of Cryptosporidium spp. among Patients with Diarrhea at Wasit Province/ Iraq - May Naji Alkhanaq; Ghadeer Thamer (Institute of Medico-legal Publications Pvt Ltd, 2022)
Cryptosporidium is an important obligate enteric protozon parasite that infects humans and wild range of animals with morbidity and mortality especially amongimmuno-suppressed individuals[1]This study carried out in al-kut city /Iraq in two major hospital Al- kut hospital for gynecology ,obstetric and pediatric and al-Karamma teaching hospital which included collection of stool samples from diarrheal patients from October / 2020 – January / 2021 , (109) stool samples taken from patients with different ages to both gender examined by microscopic examination(Modified ziehl nelson) and multiplex PCR technique, the results showed the percentage of cryptosporidium spp. infection by using M.Z.N stain was 44(40.4%) while by using PCR technique was 38(39.6%) and 4(4.2%) for C.parvum and C.hominis respectively .The rate of infection is significantly associated with residence when using M.Z.N stain and PCR for C.parvum, also significant associate among those who >5 years old. water source for drinking were significant associated factors, other factors (gender, education level) Showed no significant association with infection, the present study aimed to detection of Cryptosporidium spp. and possible association between the infection and some risk factors by using microscopic examination and detecting DNA of Cryptosporidium parasite by multiplex PCR technique.